(untitled) (Letras & Letras, 2014)
This paper discusses the grammatical category of modality and the variety of linguistic resources available for the expression of it and presents a research that aimed at analyzing the expression of modality through the use of adverbs in academic writing. More specifically, the study presented investigated how Brazilian learners of English express modality through adverbs in their academic essays. Two corpora were used: a sub-corpus taken from the Corpus of Brazilian Learners of English (CABrI) and another sub-corpus taken from the Louvain Corpus of Native English Essays (LOCNESS). The prevalent adverbial items found in both corpora were identified and described, using Corpus Linguistics tools. The analysis conducted revealed the rigidity of the expression of modality through adverbs in the learners’ written discourse as opposed to a more varied way of this expression in the native speakers’ data. This paper also discusses the way native speakers and learners differ in their written production and the possible pedagogical implications of these findings.